Pengaruh Overhaul Terhadap Performa Sistem Pelumasan Air Heater - Eko Sulistyo; M. Arif Mintorogo (Sekolah Tinggi Teknik - PLN, 2015)
In every operation, every piece of equipment a Steam Power (power plant) has a very important role to support the continuity of the process of production of electric power. Reliability and resilience of an equipment in a generating unit is the responsibility of all employees are encouraged that work in the company. At one plant often found damage during overhaul and the unit is operating. Air Preheater is one such example, which often arise various problems with age operates. The pressure drop Lube Oil Pump into a new problem in the Air Preheater, the impact of these problems resulted in Air Preheater can not operate optimally, and the impact of the worst is a unit trip (shutdown), which means the unit stops to produce electricity because of the disruption in one engine plant, of course, it will cause harm to the company. Experience analysis, and manual book is a guide to solving problems every time a unit of power generation, as well as the precision and patience is needed to see clearly how the problem occurred.